Pregnancy and parturition after hip arthroplasty. Issue 6 (December 2022) - Oliviero, Antonio; Aicale, Rocco; Maffulli, Nicola
Abstract: Background: The indications for total hip arthroplasty (THA) have become more widespread. Of the patients receiving a THA, some will be women with child-bearing potential. There has been little research into the effects of pregnancy and parturition on THA, and the effect of THA on pregnancy and parturition. Methods: A systematic search in different database, to December 2020, was performed to define the effects of pregnancy and parturition on THA, and the effect of THA on pregnancy and parturition. Seven suitable studies were identified. Results: Following a THA, there appear to be no harmful effects on subsequent pregnancies with regards to either the health of the mother or baby. There is no increase in pregnancy complications, or difficulties in labour arising from the THA. Some women and their obstetricians may opt for a pre-emptive Caesarian section, but there is no scientific basis for this line of action. The state of pregnancy in turn appears to have no harmful effects on the THA. Conclusion: Further research will be useful to better understand which materials and which types of prostheses to use in young women of childbearing age to ensure maximum safety for pregnancy and childbirth.